Effects of omalizumab in severe asthmatics across ages: A real life Italian experience. (October 2016) - Sposato, B.; Scalese, M.; Latorre, M.; Scichilone, N.; Matucci, A.; Milanese, M.; Masieri, S.; Rolla, G.; Steinhilber, G.; Rosati, Y.; Vultaggio, A.; Folletti, I.; et al.
Abstract: Background: This retrospective study aimed at evaluating long-term effects of Omalizumab in elderly asthmatics in a real-life setting. Methods: 105 consecutive severe asthmatics (GINA step 4–5; mean FEV1 % predicted:66 ± 15.7) treated with Omalizumab for at least 1 year (treatment mean duration 35.1 ± 21.7 months) were divided into 3 groups according to their age at Omalizumab treatment onset: 18–39, 40–64 and ≥ 65 years. Results: Comorbidities, number of overweight/obese subjects and patients with late-onset asthma were more frequent among older people. A similar reduction of inhaled corticosteroids dosage and SABA on-demand therapy was observed in all groups during Omalizumab treatment; a similar FEV1 increased was also observed. Asthma Control Test (ACT) improved significantly (p < 0.001) in the three groups, increasing from 15 [IQR:12-18] to 24 [IQR:22-25] in younger subjects, from 14 [IQR:10-16] to 21 [IQR:20-23] in the 40-64-year-group and from 15 [IQR:12-16] to 20 [IQR:18-22] in elderly patients where improvement was lower (p = 0.039) compared to younger people. Asthma exacerbations decreased significantly after Omalizumab but the percentage of exacerbation-free patients was higher in younger people (76.9%) compared to middle aged patients (49.2%) and the elderly (29%) (p = 0.049). After Omalizumab treatment, the risk for exacerbations was lower in subjects aged 40–64 (OR = 0.284 [CI95% = 0.098–0.826], p = 0.021) and 18–39 (OR = 0.133 [CI95% = 0.026–0.678], p = 0.015), compared to elderly asthmatics. Also, a significantly reduced ACT improvement (β = −1.070; p = 0.046) passing from each age class was observed. Conclusion: Omalizumab improves all asthma outcomes independently of age, although the magnitude of the effects observed in the elderly seems to be lower than in the other age groups. Highlights: Omalizumab improved all asthma outcomes independently of age. However the magnitude of improvement in the elderly may be lower. Obesity, comorbidities, the late-onset-asthma and "the senescence" may explain this lower efficacy.